Room Temperature Hydrogen Production from Ethanol over CeNiXHZOY Nano‐Oxyhydride Catalysts. Issue 8 (21st May 2013) - Fang, Wenhao; Pirez, Cyril; Paul, Sébastien; Capron, Mickaël; Jobic, Hervé; Dumeignil, Franck; Jalowiecki‐Duhamel, Louise
Abstract CeNiXHZOY nano‐oxyhydride catalysts were developed for the highly efficient sustainable hydrogen production from ethanol and water in the oxidative steam reforming reaction. After an in situ treatment in hydrogen in the temperature range of 200–300 °C, the cerium–nickel binary mixed oxides became hydrogen reservoirs, which were called oxyhydrides, in the presence of hydrogen species of the hydride nature in the anionic vacancies of mixed oxides. A novel technology was developed for the room temperature hydrogen production by using the chemical energy released from the reaction between CeNiXHZOY nano‐oxyhydride catalysts and oxygen, which completely converted ethanol specifically at 60 °C (oven temperature) and simultaneously produced hydrogen, carbon dioxide, and carbon monoxide along with small amounts of methane and ethanal. CeNiXHZOY nano‐oxyhydride catalysts demonstrated excellent catalytic stability, which was attributed to the graphitic filamentous carbon formed during the reaction. The unique activation phenomenon of the reaction (a huge variation in the temperature between the catalyst bed and the oven) was demonstrated in detail. Finally, the correlations among the catalyst properties, the catalytic performances, and the characterizations were thoroughly discussed.